Vem pra UFMS Program: Popularizing Science ad Promoting Sustainbale Development Goals (SDGs) - de Alcantara, Naiade Valenzuela; de Godoi, Rozana Vanessa Fagundes Valentim; Gasques, Lia Raquel Toledo Brambilla; Banyasz, Ana Paula; de Carvalho, Leonardo Chaves; Costa, Joao Vitor; Orue, Cris Almeida; Melo, Jefferson Silva de Padua; Itavo, Camila Celeste Brandao Ferreira; de Souza, Albert Schiaveto (Universitas Diponegoro, 2025)
The Federal University of Mato Grosso do Sul (UFMS), through the “Vem pra UFMS” (Come to UFMS) Program, promotes access to knowledge, science, and academic culture. This article aims to analyze how the program has contributed to the implementation of the United Nations Sustainable Development Goals (SDGs) within the context of higher education (HE). By disseminating courses, popularizing science, and presenting UFMS's teaching, research, extension, and innovation spaces, the program strengthens the connection between university and society. Its initiatives include several projects such as “Thinking About the Future”, “Science for What?”, and the “UFMS Preparatory Course”, which expands the democratization of HE by exposing high school students to academic and professional opportunities, thereby reducing inequalities. Complementary projects such as “Science in Schools”, “Science Pills”, and the “Science Park” foster the popularization of science, building more informed communities prepared to address global challenges while promoting innovation and sustainability. The “UFMS Museum of Science and Technology” further contributes to these efforts by strengthening scientific and technological culture. Methodologically, the study adopted a qualitative approach, using secondary data from institutional reports, websites, and social media to evaluate the program’s impact and its contribution to the SDGs. Findings reveal that the program encompasses seven specific actions directly linked to SDGs 4 (4.1, 4.3, 4.4, 4.7) and 10 (10.2), and reached more than 50 schools and benefited over 11,540 people. These initiatives highlight the transformative role of UFMS in education and sustainable development, demonstrating how higher education institutions can positively influence society by integrating the SDGs into their practices.